Distraksi Boneka Tangan untuk Injeksi Intravena - Vatanjani, Yossina; Irdawati, Irdawati (Journal of Telenursing (JOTING), 2024)
This study aimed to divert children's attention from the hospital environment, which often triggers anxiety, particularly during medical procedures such as infusions or injections. The method used was a case study approach within the nursing process framework. The results showed a significant reduction in anxiety and pain levels following the intervention, highlighting the effectiveness of hand puppet therapy as a simple yet impactful distraction technique. The conclusion of this study confirms that distraction therapy using hand puppets has a significant positive impact on the subjects, as evidenced by the notable differences in measurements taken before and after the intervention. Keywords: Pediatric Anxiety, Hand Puppet Therapy, Distraction Therapy